2013
DOI: 10.3109/13693786.2012.752878
|View full text |Cite
|
Sign up to set email alerts
|

Azole-resistantCandida albicansfrom a wild Brazilian porcupine (Coendou prehensilis): a sign of an environmental imbalance?

Abstract: This study aimed at evaluating the in vitro antifungal susceptibility of Candida albicans isolates obtained during necropsy of a wild Brazilian porcupine and the mechanism of azole resistance. Initially, we investigated the in vitro susceptibility of the three isolates to amphotericin B, caspofungin, fluconazole, itraconazole, ketoconazole and voriconazole. Afterwards, three sub-inhibitory concentrations (47, 21 and 12 mg/l) of promethazine, an efflux pump inhibitor, were tested in combination with the antifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 34 publications
2
38
0
3
Order By: Relevance
“…This study firstly demonstrates that the combinations of FLZ or VOR with HAL and/or PTZ increased the susceptibility of M. furfur and M. pachydermatis to azoles, suggesting that the drug efflux pumps might be involved in the defence mechanism of Malassezia yeasts against these drugs. Indeed HAL, PTZ and CYS inhibit, directly or indirectly, the activities of the fungal membrane efflux pumps, possibly increasing the susceptibility to antifungal drugs or to reverse azole resistance, as demonstrated for Candida spp …”
Section: Discussionmentioning
confidence: 95%
“…This study firstly demonstrates that the combinations of FLZ or VOR with HAL and/or PTZ increased the susceptibility of M. furfur and M. pachydermatis to azoles, suggesting that the drug efflux pumps might be involved in the defence mechanism of Malassezia yeasts against these drugs. Indeed HAL, PTZ and CYS inhibit, directly or indirectly, the activities of the fungal membrane efflux pumps, possibly increasing the susceptibility to antifungal drugs or to reverse azole resistance, as demonstrated for Candida spp …”
Section: Discussionmentioning
confidence: 95%
“…It has also been reported that azole‐resistant Candida isolates have been found in lake water and in a porcupine in Brazil. The resistance were mediated by efflux pumps . Whether these findings have implications for human infection is unknown as our study was not designed to reveal associations between agricultural azoles and candidaemia or Candida resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, overgrowth of these microbes can cause superficial mycoses, invasive mucosal infections, and disseminated systemic disease, particularly in AIDS patients, transplant recipients, and other immunocompromised people (2,3). It is well documented that the emergence of drug-resistant C. albicans is increasing at an alarming pace (4)(5)(6). Therefore, the need for effective anticandidal therapy is increasing, as the available drugs are still very restricted.…”
mentioning
confidence: 99%